2022
DOI: 10.1128/mmbr.00029-22
|View full text |Cite
|
Sign up to set email alerts
|

FabT, a Bacterial Transcriptional Repressor That Limits Futile Fatty Acid Biosynthesis

Abstract: Phospholipids are vital membrane constituents that determine cell functions and interactions with the environment. For bacterial pathogens, rapid adjustment of phospholipid composition to changing conditions during infection can be crucial for growth and survival. Fatty acid synthesis (FASII) regulators are central to this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 51 publications
(135 reference statements)
0
14
0
Order By: Relevance
“…The synthesis of lipids is an intricate process regulated by multiple enzymes. Among these, FAS is a vital participant mainly contributing to fatty acid synthesis and its functional characterization has been reported in bacteria [ 18 ] and fungi [ 19 ]. However, the identification and characterization of FAS in insects have still received less attention.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of lipids is an intricate process regulated by multiple enzymes. Among these, FAS is a vital participant mainly contributing to fatty acid synthesis and its functional characterization has been reported in bacteria [ 18 ] and fungi [ 19 ]. However, the identification and characterization of FAS in insects have still received less attention.…”
Section: Discussionmentioning
confidence: 99%
“…FabT is present in streptococci, enterococci and lactococci. FabT belongs to the MarR family of regulators [for review, [ 16 ]]. The expression of the other fakB genes is not controlled by FabT in the M1 strain [ 15 ] and a FASII coregulation may shed light on the function of the protein.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that fakB4 may be directly controlled by FabT. Consensus FabT binding sequences are found along the FASII locus, which includes fabT [[ 16 ], and references herein]. We sought whether one was also present downstream from the fakB4 transcription start site previously described [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, proteomic analysis indicated that exposure to a low concentration of H5−23 (1/2× MIC) led to a significant upregulation of proteins (fabZ1, fabI, fabG, and accD) associated with fatty acid metabolism and synthesis pathways. 28,29 Interestingly, the nonphosphorylated form of YycF inhibits the transcription of the fabT repressor and controls the fatty acid biosynthesis in Streptococcus pneumoniae by regulating the expression of fab genes. 30,31 These findings suggest a potential interplay among membrane metabolism, fatty acid metabolism, and the YycFG TCS signaling pathway.…”
Section: Synergistic Effect Of H5−23 In Combination Withmentioning
confidence: 99%